Quantum-Behaved Bat Algorithm for Combined Economic Emission Dispatch Problem with Valve-Point Effect - Mahdi, F.P. (Springer Verlag, 2018)
Combined economic emission dispatch (CEED) is a multi-objective optimization problem that deals with the minimization of total fuel cost and total emission of hazardous gases in thermal power generation system, while satisfying all equal and inequality constraints. In this research, quantum-behaved bat algorithm (QBA) is proposed and applied to solve non-linear multi-objective CEED problem. Valve-point effect is considered along with CEED as a practical constraint of power generation system. QBA is applied to 10-unit power generation system and compared separately as single objective economic and emission dispatch problems as well as multi-objective CEED problem with other existing methods like ABCPSO, DE, NSGA-II, SPEA-2 and SA. The obtained results and comparison of results demonstrate the power of QBA in terms of solution quality, convergence characteristics and computational efficiency. Â© Springer International Publishing AG 2018.